The H-index of a network node and its relation to degree and coreness - Linyuan Lü (Nature Portfolio, 2016)
Identifying influential nodes in networks is important for the understanding of their structure and function, but there are several so far unrelated measures to assess this. Here, the authors unfold relations among knows criteria and construct a family of indices that interpolate between degree and coreness.